Face Mask Wearing and Hand Washing Behavior on the Prevention of COVID-19 Infection: A Meta-Analysis - Andi Siswanto; Bhisma Murti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2022)
Background: People infected with the COVID-19 virus can infect others through close droplets, these droplets are water-filled particles with a diameter of >5 m - 10 m. ways to reduce or contract COVID-19 by wearing a mask and washing hands both with soap and hand sanitizer. This study aimed to determine the effect of wearing masks and washing hands on the transmission of COVID-19.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2020-2021 using databases from PubMed, Science direct, and Google Schoolar. The article search was carried out taking into account the eligibility criteria defined in the PICO model. Population= community. Intervention= use masks and wash hands. Comparison= do not use masks and wash hands. Outcome= infection with COVID-19. The keywords used are "face mask OR wearing mask AND hand hygiene OR hand washing AND coronavirus OR covid19 OR SAR-CoV-2 AND adjusted odds ratio". Based on the database, there are 17 articles that meet the inclusion criteria. The analysis was carried out using software RevMan 5.3.Results: Meta-analyses were conducted on 17 articles from Bangladesh, Ethiopia, Japan, China, Australia, Greece, Taiwan, and Ghana. The results of data processing show that using a mask can reduce 0.48 times than not wearing a mask at all, the results are statistically significant (aOR= 0.48; 95% CI= 0.31 to 0.76; p = 0.002) and hand washing can reduce 0.42 times than people who did not wash their hands at all with either soap or hand sanitizer, these results were statistically significant (aOR= 0.42; 95% CI= 0.26 to 0.68; p< 0.001).Conclusion: The results of this meta-analysis concluded that the use of masks and washing hands during the pandemic can prevent the transmission of COVID-19.Keywords: masks, wash hands, COVID-19.Correspondence:Andi Siswanto. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: andisiswae@gmail.com. Mobile: +62 813-2923-8155.Journal of Health Promotion and Behavior (2022), 07(03): 182-196DOI: https://doi.org/10.26911/thejhpb.2022.07.03.02